2021
DOI: 10.34306/conferenceseries.v3i2.472
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Competence, Job Stress And Perceived Organizational Support On Employee Performance With Organizational Commitments As Intervening Variables

Abstract: This study aims to analyze the effect of Competence, Job Sress, and Perceptual Organizational Support on Performance with Organizational Commitment as an Intervening Variable on Tanjungpinang City government employees. This type of research is associative causality. This research was conducted using a survey method by distributing questionnaires from government agencies in the Tanjungpinang City Government. The population of this study was all Regional Apparatus Organizations in Tanjungpinang City Government, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…It means that employees' organizational commitment does not affect their performance positively or negatively. This study supports previous research conducted by Sariani et al (2021), Indarti et al (2017), and Dewi et al (2021 that found no significant influence of Organizational Commitment on Employee Performance. Manifest variables that indicate the affective commitment dimension, M1.3, M1.1, and M1.2, respectively, have the highest outer loading values, indicating that affective commitment among employees is the most representative variable for organizational commitment.…”
Section: Discussionsupporting
confidence: 92%
“…It means that employees' organizational commitment does not affect their performance positively or negatively. This study supports previous research conducted by Sariani et al (2021), Indarti et al (2017), and Dewi et al (2021 that found no significant influence of Organizational Commitment on Employee Performance. Manifest variables that indicate the affective commitment dimension, M1.3, M1.1, and M1.2, respectively, have the highest outer loading values, indicating that affective commitment among employees is the most representative variable for organizational commitment.…”
Section: Discussionsupporting
confidence: 92%